Puncture resistance and mechanical properties of graphene oxide reinforced natural rubber latex - Chong, Kai Yin; Chia, Chin Hua; Sarani Zakaria; Pham, Thi Hao; David Lucas; Chin, Siew Xian (Penerbit Universiti Kebangsaan Malaysia, 2018)
Natural rubber (NR) latex gloves are widely used as a very important barrier for healthcare workers. However, they can still be perforated easily by sharp devices and instruments. The aim of this study was to investigate the effect of the addition of graphene oxide (GO) to low-ammonia NR latex on its puncture resistance, mechanical properties and thermal stability. GO was synthesized using modified Hummers’ reaction. The produced GO was mixed into the NR latex solution at various doses (0.01-1.0 wt. %), followed by a coagulant dipping process using ceramic plates to produce film samples. Puncture resistance was enhanced by 12% with 1.0 wt. % GO/NR. Also, the incorporation of GO improved the stress at 300% and 500%, the modulus at 300% and 500% and the tear strength of low-ammonia NR latex films.